Case Report: Omalizumab combined with voriconazole for the treatment of ABPA complicating IPA: a case report - Zhao, Tingrui; Chen, Yukai; Sun, He (Frontiers in Pharmacology, 2025)
Aspergillus invading hosts may manifest as Allergic bronchopulmonary aspergillosis (ABPA) or invasive pulmonary aspergillosis (IPA) in individuals with varying immune statuses. ABPA predominantly occurs in severe asthma patients, whereas IPA is typically observed in immunocompromised individuals. ABPA management centers on glucocorticoids to mitigate hypersensitivity-driven inflammation, while IPA requires aggressive antifungal therapy. Concurrent ABPA and IPA presents a therapeutic dilemma, as glucocorticoids use may exacerbate fungal dissemination, while antifungal agents alone inadequately address the allergic component. Adjusting treatment strategies to balance immunosuppression to control ABPA with sufficient antifungal coverage for IPA is critical step. The case report presents an innovative therapeutic strategy for a 73-year-old female with co-existing ABPA and IPA. After suboptimal clinical response to conventional glucocorticoid-antifungal therapy, we implemented a guideline-aligned, evidence-based regimen combining omalizumab with voriconazole. While this dual therapy achieved clinical stabilization, persistently elevated serum IgE (>5000 IU/mL). By reviewing the literature and comparing the differences between the mechanisms of omalizumab and dupilumab, the treatment was finally changed from omalizumab to dupilumab and followed up. This case is also a practice guided by ISHAM guidelines while pioneering a mechanism-driven transition from omalizumab to dupilumab in ABPA-IPA co-management. In order to provide guidance for the treatment of ABPA-IPA disease.